Developing Islamic Social Entrepreneurship Through Crowdfunding Waqf Model - Mansyur, Abdurrahman; Isman, Ainul Fatha (Al-Mashrafiyah: Jurnal Ekonomi, Keuangan, dan Perbankan Syariah, 2024)
This study aims to analyze the urgency of developing Islamic social enterprise and conceptualize its development by integrating financial technology and Islamic charity. This study uses a qualitative method with an inductive reasoning method. The results of this study demonstrate the urgency of Islamic social enterprise as a business concept to create sustainable value for society to overcome social problems. The advantages of crowdfunding for Islamic social entrepreneurship are provides access to capital for various small businesses, reach many local and international investors, promotes innovation, and supports business growth. This research formulates a waqf model for Islamic social entrepreneurship. This platform acts as a medium that brings together funders, funds, and managers. This concept is in line with Islamic values that characterize Islamic social entrepreneurship. The Waqf crowdfunding model for the development of Islamic social entrepreneurship can providing flexibility and funding to optimize potential businesses. The waqf crowdfunding model can contribute to developing social entrepreneurship potential in Muslim countries.